Residential greenness is differentially associated with childhood allergic rhinitis and aeroallergen sensitization in seven birth cohorts. Issue 10 (6th May 2016) - Fuertes, E.; Markevych, I.; Bowatte, G.; Gruzieva, O.; Gehring, U.; Becker, A.; Berdel, D.; von Berg, A.; Bergström, A.; Brauer, M.; Brunekreef, B.; Brüske, I.; et al.
Abstract: Background: The prevalence of allergic rhinitis is high, but the role of environmental factors remains unclear. We examined cohort‐specific and combined associations of residential greenness with allergic rhinitis and aeroallergen sensitization based on individual data from Swedish (BAMSE), Australian (MACS), Dutch (PIAMA), Canadian (CAPPS and SAGE), and German (GINIplus and LISAplus) birth cohorts ( n = 13 016). Methods: Allergic rhinitis (doctor diagnosis/symptoms) and aeroallergen sensitization were assessed in children aged 6–8 years in six cohorts and 10–12 years in five cohorts. Residential greenness was defined as the mean Normalized Difference Vegetation Index (NDVI) in a 500‐m buffer around the home address at the time of health assessment. Cohort‐specific associations per 0.2 unit increase in NDVI were assessed using logistic regression models and combined in a random‐effects meta‐analysis. Results: Greenness in a 500‐m buffer was positively associated with allergic rhinitis at 6–8 years in BAMSE (odds ratio = 1.42, 95% confidence interval [1.13, 1.79]) and GINI/LISA South (1.69 [1.19, 2.41]) but inversely associated in GINI/LISA North (0.61 [0.36, 1.01]) and PIAMA (0.67 [0.47, 0.95]). Effect estimates in CAPPS and SAGE were also conflicting but not significant (0.63 [0.32, 1.24] and 1.31 [0.81, 2.12], respectively). All meta‐analyses were nonsignificant. Results were similar for aeroallergen sensitization at 6–8 years and both outcomes at 10–12 years. Stratification by NO2 concentrations, population density, an urban vs rural marker, and moving did not reveal consistent trends within subgroups. Conclusion: Although residential greenness appears to be associated with childhood allergic rhinitis and aeroallergen sensitization, the effect direction varies by location.